2022
DOI: 10.1159/000526296
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Anti-Demodex Strategies: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> <i>Demodex</i> mites are related to some inflammatory diseases such as rosacea and blepharitis and could be harmful in patients with immunodeficiency or immunosuppression, especially notable in patients using biologic like dupilumab. In order to have an objective observation of different anti-<i>Demodex</i> strategies, we conducted this study, based on interventional clinical evidence with quantified <i>Demodex</i> mite data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In the present case, topical metronidazole was chosen due to ease of use, wish to avoid further systemic therapy, and insurance coverage. Although “off-label,” the use of topical metronidazole is a long-accepted treatment of Demodex, for which there are a variety of treatment options (many off-label), from topical to systemic therapies, including systemic ivermectin.. 14 In July 2023, lotilaner ophthalmic solution became the first Food and Drug Administration (FDA)-approved therapeutic for Demodex blepharitis. Phase 3 trial of lotilaner ophthalmic solution versus vehicle control showed collarette cure at 56% versus 12.5% ( p < 0.0001) and mite eradication at 51.8% versus 14.6% ( p < 0.0001) after 6 weeks of twice-daily treatment in patients with Demodex blepharitis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, topical metronidazole was chosen due to ease of use, wish to avoid further systemic therapy, and insurance coverage. Although “off-label,” the use of topical metronidazole is a long-accepted treatment of Demodex, for which there are a variety of treatment options (many off-label), from topical to systemic therapies, including systemic ivermectin.. 14 In July 2023, lotilaner ophthalmic solution became the first Food and Drug Administration (FDA)-approved therapeutic for Demodex blepharitis. Phase 3 trial of lotilaner ophthalmic solution versus vehicle control showed collarette cure at 56% versus 12.5% ( p < 0.0001) and mite eradication at 51.8% versus 14.6% ( p < 0.0001) after 6 weeks of twice-daily treatment in patients with Demodex blepharitis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inflammatory reaction could be insufficient to eradicate Demodex mites as some of the infiltrating T-cells have become dysfunctional, so that polymorphisms in dendritic cells would explain the different susceptibility to Demodex antigens ( Forton, 2020 ). On the other hand, a recent meta-analysis evaluating the efficacy of different anti- Demodex treatments concluded that topical and systemic ivermectin, topical ivermectin-metronidazole, and topical tea tree oil, are promising anti- Demodex interventions ( Li et al, 2023 ). In addition, topical ivermectin 1% treatment for 12 weeks significantly decreased Demodex density and downregulated IL-8, LL-37, TLR-4, human β-defensin 3 (HBD3), and tumor necrosis factor α (TNF-α) gene expression, implicating anti-inflammatory effects along improving clinical course of rosacea ( Schaller et al, 2017b ).…”
Section: Pathophysiology Of Rosaceamentioning
confidence: 99%
“…The determination of mite density can be conducted through direct microscopic examination or standardized skin surface biopsy [20]. Treatment options include topical and systemic ivermectin, topical and systemic metronidazole, and topical and light therapy, such as intense pulsed light (IPL) [11,27].…”
Section: Demodicosismentioning
confidence: 99%